COMPOSITION ANALYSIS OF IRRIGATED LAND USE SYSTEM AND ITS STATISTICAL EVALUATION (World Economics and Finance Bulletin, 2023)
In this article, the structural structure of the irrigated land use system is explained in detail and it is statistically evaluated. Also, practical recommendations for solving problems related to the use of irrigated land and the use of irrigated land have been developed.
Keywords: Irrigated lands; land and water resources; economic-ecological efficiency